The physiological effects of daily cold-water immersion on 5-day tournament performance in international standard youth field-hockey players - Krueger, M.; Costello, J. T.; Stenzel, M.; Mester, J.; Wahl, P. (European Journal of Applied Physiology, 2020)
Purpose: This study examined the effects of daily post-exercise cold-water immersion (CWI) on match performance, perceptual recovery, and biomarkers of muscle damage and metabolic load during a 5-day international tournament of elite youth field-hockey players. Methods: The entire German under-18 national squad (n = 18) was randomly assigned to a daily CWI- (5-min at ~ 6 °C; excluding the head; n = 9) or passive recovery (CON; n = 9) intervention. Training and match performance were assessed using a GPS-tracking system and perceived exertion (RPE). Daily ratings of delayed onset muscle soreness (DOMS), perceived stress and recovery, quality of sleep, heart-rate recovery and serum creatine kinase (CK), lactate dehydrogenase, and urea nitrogen were also recorded. Repeated-sprint ability (RSA) and counter-movement jump (CMJ) were carried out on days 1 and 5. Results: There was no significance between intervention differences in time-on pitch, total distance, velocity zones, and accelerometer-base parameters during match performance (all p > 0.05). DOMS (p < 0.01), RPE (p < 0.01), and CK (p < 0.01) were significantly elevated over the course of the tournament; however, no between-intervention effects were observed (all p > 0.05). Both groups were able to maintain RSA and CMJ (all p > 0.05). Conclusion: In conclusion, daily post-exercise CWI did not improve match performance, perceptual recovery, or biomarkers of muscle damage and metabolic load in elite youth field-hockey players.